The Corelation Knowledge Be About Pregnancy Maternal Care (ANC) Towards Antenatal Care Mojoroto Village District Kediri - darmayanti, Rofik; Betristasia Puspitasari (Jurnal EduHealth, 2024)
Antenatal  care  (ANC)  is   treatment  given  to  mother   during   pregnancy. Antenatal  care  is  effort together both health  officer  and pregnant mother, that is consist  of  check  pregnancy  and  correlation  effort  to deviation  had  found.The important  of  antenatal  care  to  guarantee  natural  process  in  order to normally, during pregnancy. The knowleg during pregnant mother is very important because can  be  influences of pregnancy, that is fetus. The purpose of research is to know the  correlation  between  knowleg  be  about   pregnancy   maternal  care  towards antenatal care. The   design   of  research  is  used  on  this  research  is correlation study, with cross – sectional  approach.  The   population  research  is  all  of pregnant  mother done  on   Mojoroto  Village   Kediri   Regency at  37 people.Total  sample   30    responden  using   purposive    sampling,   Independen   variable (Knowledge be abaut  pregnancy maternal care) and  dependent  variable (Antenatal regularly). The  collecting  data  using  questionnaire  done  on 14 - 26 November 2023, then processing data by editing, coding, tabulating, scoring. The  result  of  research got  that knowledge  be abaut pregnancy maternal care have  good   criteria  is  20  responden  (66,6%)  and  visited antenatal care toward regulare criteria are 19 responden (63,3%). Statistics test Chi Square p value 0,001 <  0,05. It  can  be  concluded  that   H1  accepted,  it   means  mat  the  correlation  between knowledg be about  pregnancy maternal care towards antenatal care. The conclusion in this research that  good  of   knowledge   would  be   caused antenatal care  regularly,  poor of  knowledge  would  be show that poor  regularly on antenatal care. So  that,  needed  lead  knowledge  maximally  to  get  antenatal care regularly in order to pregnancy of mother to be normal.